Expression and function of the Transforming Growth Factor‐b system in the human and rat enteric nervous system. Issue 7 (27th March 2013) - Hagl, C.; Schäfer, K.‐H.; Hellwig, I.; Barrenschee, M.; Harde, J.; Holtmann, M.; Porschek, S.; Egberts, J.‐H.; Becker, T.; Wedel, T.; Böttner, M.
Abstract: Background: Transforming growth factor‐betas (TGF‐bs) are pleiotropic growth factors exerting neurotrophic functions upon various neuronal populations of the central nervous system. In contrast, the role of TGF‐b isoforms in the enteric nervous system (ENS) is largely unknown. We therefore analyzed the gene expression pattern of the TGF‐b system in the human colon and in rat myenteric plexus, and smooth muscle cell cultures and determined the effect of TGF‐b isoforms on neuronal differentiation. Methods: Human colonic samples as well as cultured rat myenteric plexus, and smooth muscle cells were assessed for mRNA expression levels of the TGF‐b system (TGF‐b1‐3, TbR‐1‐3) by qPCR. The colonic wall was separated into mucosa and tunica muscularis and enteric ganglia were isolated by laser microdissection (LMD) to allow site‐specific gene expression analysis. Effects of TGF‐b isoforms on neurite outgrowth and branching pattern of cultured myenteric neurons were monitored. Key Results: mRNA expression of the TGF‐b system was detected in all compartments of the human colonic wall as well as in LMD‐isolated myenteric ganglia. Cultured myenteric neurons and smooth muscle cells of rat intestine also showed mRNA expression of all ligands and receptors. Transforming growth factor‐b2 treatment increased neurite length and branching pattern in cultured myenteric neurons. Conclusions & Inferences: The TGF‐b system is abundantly expressed in the human and rat ENS arguing for an auto‐/paracrine function of this system on enteric neurons. Transforming growth factor‐b2 promotes neuronal differentiation and plasticity characterizing this molecule as a relevant neurotrophic factor for the ENS.